Description of Knowledge, Attitudes, Behavior of Snacking Habits and Nutritional Status of Students at MI Darun Najah Kloposepuluh Sukodono Sidoarjo - Marisa Millatal Haq; Ani Intiyati; Annas Buanasita; Riezky Faisal Nugroho (Politeknik Kesehatan Kemenkes Surabaya, 2024)
Street food is food that is sold and served by street vendors on the side of the road and in public places, which can be eaten directly without further processing or preparation. This study aims to describe the level of knowledge, attitudes, behavior, eating habits, and nutritional status of students at MI Darun Najah Klopoten Sukodono Sidoarjo. This research method uses a descriptive method. The total population of this study was 311 students in grades 4, 5, and 6 and a sample of 56 students was taken using Proportionate Stratified Random Sampling. Data collection was carried out through interviews with knowledge questionnaires, attitudes, FFQ forms, and anthropometric measurements. From the results of the study, most of the students had a sufficient category of knowledge (64.3%), good attitude (71.4%), frequent snacking behavior (53.6%), and good nutritional status (55.4%). From this, it can be concluded that most students still have sufficient knowledge and behavior of frequent snacking habits. It is recommended that the school hold outreach to students regarding information on snacks and nutrition and how to eat good and healthy snacks. School canteens are also expected to provide nutritious snacks.